The Business Strategy Development: A Case Study at PT Hijrah Gizi Hewani - Mahdi Rajab, Fadil; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2017)
Abstract - PT Hijrah Gizi Hewani established since 1991, it is a meat distributor company that sell the product to some several kind of company in Jakarta for example like hotels, restaurants, catering, etc. In 2015, sales of PT Hijrah Gizi Hewani has decreased when compared to the average sales in the last three years. Meat prices rose sharply in 2015 and are likely to continue to rise until Eid in 2016. This is because the government reduce the number of quota imported meat that can be sold in Indonesia. In the middle of 2016, the government slowly opened and adding the import quotas, in September 2016 the government officially allowing the imported meat from India to be sold in Indonesia, that meat is distributed only through BULOG. This makes the importers and distributors be in one level in order to get the imported meat from India .To overcome this, the authors try to formulate the business strategies that will be submitted to PT Hijrah Gizi Hewani. Based on the results of the formulation of the author, a suitable strategy to be applied to the PT Hijrah Gizi Hewani is a cost leadership strategy, where the products that being offered at the distributor level is similar with the other, the differentiator factors are come from price, quality of service and availability of products, particularly in certain brands that become customerâ€™s favorite. In addition, there are some internal restructuring of companies in order to improve the effectiveness and cost efficiency in the process of business activities, where competition is become more tight that caused by the entry of imported meat from India who makes the distributor must also be ready to compete with importers. Â Keywords: Business Strategy, Strategy Formulation, Market Analysis